Significance of social media on woman education and justice: A review from South Asian context - Montaha, Sidratul; Chowdhury, Tasin Safwath; Kabir, G M Ikramul; Uddin, Md Minhaz (Journal of New Media and Mass Communication, 2023)
The initial purpose of this study was to review the impact of social media on women’s education as well as education and justice in South Asian countries. Social media is actively contributing to the advancement of women’s education and justice. It has made education more accessible and convenient, and it has brought people from all over the world together to support the oppressed in the pursuit of justice. This is the first time an investigation using secondary sources of information in the research area, such as South Asian nations, has ever been looked at in relation to that specific research issue. Better access to social media, efficiency, ensuring justice, better and higher-quality education, and modernization are all improved by this review. This study also makes a contribution by highlighting the value and favorable perceptions of social media in justice and education, as well as social awareness. Limitations exist, and future research should focus on quantitative strategies that benefit stakeholders.